2017
DOI: 10.1098/rsfs.2016.0086
|View full text |Cite
|
Sign up to set email alerts
|

Foraging in an unsteady world: bumblebee flight performance in field-realistic turbulence

Abstract: Natural environments are characterized by variable wind that can pose significant challenges for flying animals and robots. However, our understanding of the flow conditions that animals experience outdoors and how these impact flight performance remains limited. Here, we combine laboratory and field experiments to characterize wind conditions encountered by foraging bumblebees in outdoor environments and test the effects of these conditions on flight. We used radio-frequency tags to track foraging activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 42 publications
4
70
0
Order By: Relevance
“…This particular intermediate value of I does not require a large number of flow realizations for any tested value of Λ, which allows keeping the computational cost within acceptable limits. Furthermore, field experiments [11] show a large flight activity of bumblebees for this value of I. Fig.…”
Section: Influence Of Turbulent Length Scales At Constant Intensitymentioning
confidence: 56%
See 1 more Smart Citation
“…This particular intermediate value of I does not require a large number of flow realizations for any tested value of Λ, which allows keeping the computational cost within acceptable limits. Furthermore, field experiments [11] show a large flight activity of bumblebees for this value of I. Fig.…”
Section: Influence Of Turbulent Length Scales At Constant Intensitymentioning
confidence: 56%
“…Vortex shedding in von Kármán wakes, however, differs from turbulence since, at moderate Reynolds numbers, vortices are shed periodically in time and the flow has strong spatial correlations. Few numerical [18] and experimental [10,11] studies addressed flapping flight in turbulent flow and estimated flow conditions at body and wings. In heavy turbulence, for example, bumblebees are highly prone to changes in roll stability and crash if roll velocity exceeds a maximum value [10].High maneuverability in flight is likely key in coping with turbulence, at the cost of low stability [26,27].…”
mentioning
confidence: 99%
“…However, recent efforts have begun to shed light on turbulence-mitigation strategies used by biological fliers [30], such as the mechanisms used by bumblebees to increase stability. One example found that bumblebees respond to turbulence with changes in wing kinematics that are both static (as in altered mean values) and dynamic (stroke by stroke) [31]. …”
Section: Turbulent Environmentsmentioning
confidence: 99%
“…Wind affects macroecological patterns of insect dispersal and migration [6,7]. Mean wind flow [8] and fluctuations (i.e., turbulence) pose biomechanical challenges [9][10][11][12][13] that push maneuverability limits in flying insects [14] and may impose energetic costs on flight [15]. The mechanical and physiological challenges posed by wind may have important effects on their interactions with plants, including herbivory [16,17], and pollinator visitation and landing [18].…”
Section: Introductionmentioning
confidence: 99%
“…While wind is thus known to have many effects on pollinator behavior and ecology, our understanding of its influence on bee abundance and plant visitation rates is limited. While extreme wind speeds restrict bee flight and foraging (reviewed in [29]), recent studies have found that wind can have either positive [30] or negligible [10,31] effects on bee abundance and activity. Some wind's variable effects could be explained by differences in pollinator sensory ecology, particularly the importance of olfactory cues for locating floral resources.…”
Section: Introductionmentioning
confidence: 99%